Reconstructive surgery in the context of Covid-19: complications in the treatment of an inguinal complex wound - Vinícius Gomes Da Silveira; Pedro Soler Coltro; Henrique Ovidio Coraspe Gonçalves; Diogo Hummel Hohl; Gabriel Maziero Alves Silva; Jayme Adriano Farina-Junior (Revista Brasileira de Cirurgia Plástica, 2020)
Introduction: At the end of 2019, the world saw the emergence of a new respiratory syndrome called Covid-19, caused by a new type of coronavirus, Sars-CoV-2. Classified as a pandemic, it has caused impacts of considerable magnitude. Case Report: A 57-year-old man developed a right inguinal wound after surgical exploration for infection of a prosthesis used in a femur-popliteal bypass. The Plastic Surgery team opted for treatment with surgical debridement associated with negative pressure therapy to prepare the wound bed. In the postoperative period, he had severe acute respiratory syndrome and suspected Covid-19, requiring intubation and intensive care. A sample for RT-PCR of Sars-CoV-2 was collected, and the medications chloroquine and azithromycin were associated with the treatment. Despite intensive treatment, the patient died. The result of the RT-PCR test for the new coronavirus was positive, being released two days after death. Discussion: The analysis of this report allows us to suppose that the patient probably contracted the new coronavirus at the hospital, as he was hospitalized for 35 days before the evolution of respiratory failure. This fact, together with its unfavorable evolution, corroborates the orientation of minimizing hospitalizations and surgical procedures as much as possible to promote more safety for the patient and the health team. Conclusion: Inpatients are susceptible to infection with the new coronavirus and can set up a group at higher risk since many of them are already weakened.